Effect of soil management systems on the rhizosphere bacterial community structure of tobacco: Continuous cropping vs. paddy-upland rotation - Wang, Peng; Yan, Shen; Zhang, Wenshui; Xie, Xiaodan; Li, Mingjie; Ren, Tianbao; Gu, Li; Zhang, Zhongyi (Frontiers in Plant Science, 2022)
Rhizosphere bacteria play important roles on soil nutrient cycling and plant growth, whose richness and diversity were influenced by soil management. However, the specific changes of tobacco rhizosphere bacteria community structure in continuous and tobacco-rice rotation cropping systems remain investigated. In this study, soil properties and rhizosphere bacterial community composition in tobacco monocropping and tobacco-rice rotation cropping systems were analyzed. Moreover, the comparison of rhizosphere bacteria community structure between tobacco continuous and tobacco-rice rotation cropping systems was performed via high throughput sequencing. The variety of rhizosphere bacteria community composition was investigated in different tobacco growth stages. The results showed that continuous tobacco cropping increased the soil soluble organic carbon (SOC), total nitrogen (TN) and other nutrients content (e.g., available phosphorus and available potassium) compared to tobacco-rice rotation cropping. But monocropping decreased bacteria alpha diversity and altered the community composition as compared with the rotation cropping. At the phylum level, Proteobacteria, Gemmatimonadetes and Bacteroidetes relative abundance increased in the continuous cropping soil, while Acidobacteria, Firmicutes and Actinobacteria relative abundance decreased. At the genera level, the dominant genus Bacillus. varied in average abundance from 12.96% in continuous cropping libraries to 6.33% in the rotation cropping libraries (p<0.05). Additionally, several other taxa such as o_Acidobacteriales. and Candidatus_Solibacter. decreased from 7.63% to 6.62% (p<0.05) and 4.52% to 2.91% (p<0.05), respectively. However, f_Gemmatimonadaceae. and c_Subgroup_6. relative abundance showed an increase of 1.46% (p<0.05) and 1.63% (p<0.05) in tobacco-rice rotation cropping system. The results of NMDS indicated that the rhizobacteria community structure differed in two cropping systems. While it showed no significant changes in tobacco prosperous long-term stage and topping stage but the rhizosphere bacteria community structure changed significantly in the mature stage.